Turkish digital linguaculture :|intertextual practices of a facebook community - Çetin, Mervenur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This discourse-based study aims to provide a perspective on online Turkish linguaculture through the practices of a Facebook Specific Interests Group (SIG) and the possible implications of these practices in context. Focusing on posts and comments of the SIG members, the study investigates how the heteroglot practices and intertextual references made through diverse semiotic resources such as text and visuals including GIFs, images, videos and emoticons, and also the original contexts where these references are used and taken from. The analysis draws on the content produced on the SIG in a 3-month data collection period. The findings of the study demonstrate that members’ linguacultural practices manifest themselves commonly in their use of figurative language, multimodal resources and English that reflect their multiliteracies. Thanks to these practices, a hybrid digital discourse and the linguaculture of the SIG are constructed through multilayered heteroglot and intertextual relations.
Keywords: Online social networks.; Facebook (Electronic resource); Language and culture -- Turkey.